THERAPEUTIC ASPECTS OF USE SYSTEM N.O.R - Dan Bosânceanu; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2014)
In the treatment of cranial-mandibular disorders and other diseases of the masticatory system should apply a therapy that has a special place as the approach and results that is called occlusal equilibration. The study is based on a sample of patients from The Department of Education of the Faculty of Dentistry Iasi, received treatment with cranial-mandibular repositioning in the last three years (2002-2004), having the purpose to evaluate the therapeutic aspects of N.O.R. systems using.